Development and validation of the health education demand scale for HPV infected patients based on KANO model - Yuying Zhang; Li Luo; Shuaihui Du; Die Hou; Yaling Zhang; Limin He; Lihua Zhou (PLoS ONE, 2025)
Objective The purpose of this study is to develop and validate the scale of health education demand of patients with HPV infection based on KANO model, so as to provide a tool for further exploring the types of health education demand and influencing factors of patients with HPV infection. Methods This study is a scale development and validation study using a three-stage cross-sectional design. In stage 1, a preliminary item pool is formed using literature review, semi-structured interviews and the Delphi method. In stage 2, six experts were invited to assess content validity. A cross-sectional survey was conducted on 1169 patients with HPV infection, Questionnaire results from 583 patients were used for exploratory factor analysis. In stage 3, the remaining 586 patients to validate the factor structure through confirmatory factor analysis. Results In stage 1, an initial 35-item scale was developed and the items were transformed positive and reverse based on KANO model. In stage 2, Exploratory factor analysis formed a scale of 28 items in 5 factors: disease information demand, social support, emotional demand, family support and health education style demand. Cronbach’s alpha was 0.940 for the entire scale and 0.763~0.908 for the five subscales in the positive items, 0.955 for the entire scale and 0.739~0.946 for the five subscales in reverse items. The content validity index of the scale: S-CVI/UA = 0.91, S-CVI/Ave = 0.98. In stage 3, the confirmatory factor analysis showed that the χ2/df, RMSEA, CFI and TLI of the positive items after four model modifications were 3.650, 0.067, 0.901, 0.888, and the SRMR value was < 0.001. The fitting of the five-factor model was good. Conclusion The KANO model based questionnaire on health education demand of HPV infected patients has good reliability and validity, and is suitable for the investigation of health education demand of HPV infected patients.